Transformasi Pembelajaran Fikih melalui Kurikulum Merdeka Belajar - Waffiq Dzil Izza Hafida; Muhammad Miftah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
This study aims to investigate a discussion on the implementation of the independent learning curriculum at madrasah tsanawiyah. This research uses a qualitative descriptive qualitative research method using the independent curriculum theory which is based on constructivism learning theory. According to the principle of independent learning, curricula can be tailored to meet the needs and abilities of students, enabling them to participate more actively and creatively in the learning process. Regarding data collection techniques, it consists of conducting interviews with fikih subject teachers. Based on the research, the independent curriculum for learning fikih at MTs Hasyim Asy'ari Bangsri has been implemented since the 2023/2024 school year, but the implementation has not been perfect. When the autonomous learning curriculum for fikih learning was implemented, a number of difficulties and issues were discovered, namely educators or teachers have the responsibility of compiling teaching modules for learning, but the teacher has not found specific reference material for making teaching modules. Information is still limited regarding fikih learning in the independent learning curriculum. Even though the ministry of religion has an independent curriculum platform called Sikurma, the Ministry of Religious Affairs' autonomous learning curriculum which includes learning fikih, has not been fully covered by this platform. Because there aren't many independent curriculum textbooks available for Islamic Religious Education in madrasahs, pupils are still using the 2013 curriculum books.